Physiological immaturity and hydropriming of parkia nitida miq. seeds with physical dormancy - Moraes, Gina Janet Vargas Pinedo; Ferraz, Isolde Dorothea Kossmann; Procópio, Lilian Costa (Ciência Florestal, 2015)
Parkia nitida (Fabaceae Mimosoideae) is a neotropical timber tree of economic e ecological importance due to its wood and the possibility of rapid growth in degraded areas. is a neotropical tree species of economic and ecological importance. That study aimed to verify if the freshly harvested seeds exhibit physiological immaturity and apply hydropriming on seeds with different degrees of imbibition to enhance the germination performance. The same seed lot was tested immediately after collection and after one year of storage. The treatments were 0, 20, 40 and 60% of partial imbibition in water at 15°C, followed by a drying period of 7 days. The seeds were sown in washed sand in the nursery (4 x 25 seeds / treatment). Seed moisture was assessed before and after imbibition, and after drying. Statistical tests ANOVA and Kruskal-Wallis showed significant difference between treatments for final germination percentage and mean germination time (p> 0.05). Fresh seeds of Parkia nitida showed 35% of normal seedling development, this value increased after one year of storage to 76%. Hydropriming of the fresh seeds was able to increase the germination to the same value as the stored seeds and reduced the mean emergence time from 7 to 4 days. The positive action of hydropriming was observed only after a partial imbibition of 20% (29 hours), longer imbibition periods significantly reduced the germination. The results indicate on a “critical imbibition level” between 20 and 40% of turgency. The need for a post-harvest maturation for Parkia nitida seeds could be overcome with hydropriming of the fresh seeds. © 2015, Universidade Federal de Santa Maria. All rights reserved.
Imaturidade fisiológica e condicionamento hídrico de sementes de parkia nitida miq com dormência física